2015
DOI: 10.1016/j.juro.2014.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Donation after Cardiac Death Pediatric En Bloc Renal Transplantation

Abstract: We report successful transplantation of a small cohort of pediatric en bloc kidneys obtained through donation after cardiac death from donors younger than 4 years. Outcomes at 1 year are comparable to those in neurological determination of death en bloc allograft recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Pediatric en bloc transplant was performed using previously described techniques . Accordingly, the immunosuppression administered was in accordance to that described in the aforementioned publication.…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric en bloc transplant was performed using previously described techniques . Accordingly, the immunosuppression administered was in accordance to that described in the aforementioned publication.…”
Section: Methodsmentioning
confidence: 99%
“…Dion et al in a recent single-centre analysis identified 21 adult recipients of EBK transplants from paediatric donors under the age of 4 years old, of which four organ pairs were obtained from DCD donors [38]. DGF ensued in 2 of 4 DCD organ recipients and 3 of 17 DBD organs.…”
Section: Use Of Paediatric Dcd Organsmentioning
confidence: 99%
“…Using national registry data, good graft outcomes were demonstrated in adult recipients. Historically, the poor outcomes found in the youngest donor kidneys transplanted into young recipients have been attributed to surgical complications, high rates of graft thrombosis, early rejection and hyperfiltration injury [1,7]. Consequently, there has been a reluctance to use the youngest donor kidneys for transplantation into young donors, with a considerable decline in paediatric recipients of young donor kidneys from 7/16 in 1963–1999 to 1/26 in 2000–2018 in our series.…”
Section: Discussionmentioning
confidence: 95%